The Role of Cold Inducible RNA-Binding Protein in Cardiac Physiology and Diseases - Peng Zhong; Peng Zhong; Peng Zhong; Jianye Peng; Zhouyan Bian; Zhouyan Bian; Zhouyan Bian; He Huang; He Huang; He Huang (Frontiers Media S.A., 2021)
Cold-inducible RNA-binding protein (CIRP) is an intracellular stress-response protein that can respond to various stress conditions by changing its expression and regulating mRNA stability. As an RNA-binding protein, CIRP modulates gene expression at the post-transcriptional level, including those genes involved in DNA repair, cellular redox metabolism, circadian rhythms, telomere maintenance, and cell survival. CIRP is expressed in a large variety of tissues, including testis, brain, lung, kidney, liver, stomach, bone marrow, and heart. Recent studies have observed the important role of CIRP in cardiac physiology and diseases. CIRP regulates cardiac electrophysiological properties such as the repolarization of cardiomyocytes, the susceptibility of atrial fibrillation, and the function of the sinoatrial node in response to stress. CIRP has also been suggested to protect cardiomyocytes from apoptosis under various stress conditions, including heart failure, high glucose conditions, as well as during extended heart preservation under hypothermic conditions. This review summarizes the findings of CIRP investigations in cardiac physiology and diseases and the underlying molecular mechanism.